2012
DOI: 10.7461/jcen.2012.14.3.186
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Subarachnoid Hemorrhage Volume and Development of Cerebral Vasospasm

Abstract: ObjectiveThe objective of this study is to verify the relationship between subarachnoid hemorrhage (SAH) volume (not Fisher grade) and development of cerebral vasospasm prospectively.MethodsPatients who visited our hospital with a diffuse or localized thick subarachnoid blood clot seen on computed tomography (CT), taken within 48 hours after SAH and the aneurysm was confirmed by CT Angiogram (CTA) from March 2010 to July 2011 were enrolled in this study. CTA was checked at least twice after admission. Angiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 21 publications
1
8
1
Order By: Relevance
“…As expected, patients diagnosed with NPM-SAH had higher Fisher scale scores ( 13 ) and a higher risk of vasospasm, ( 14 , 15 ) which is in line with notion that patients with an aggressive clinical presentation and a greater amount of blood detected in the subarachnoid space have a poorer prognosis. ( 16 )…”
Section: Discussionsupporting
confidence: 84%
“…As expected, patients diagnosed with NPM-SAH had higher Fisher scale scores ( 13 ) and a higher risk of vasospasm, ( 14 , 15 ) which is in line with notion that patients with an aggressive clinical presentation and a greater amount of blood detected in the subarachnoid space have a poorer prognosis. ( 16 )…”
Section: Discussionsupporting
confidence: 84%
“…Concern for the collection of blood products in the subarachnoid space cannot be understated as the degree of SAH is frequently considered the most important factor influencing vasospasm after aSAH. One recent prospective study demonstrated an average SAH volume of 17.67±5.18ml in patients who developed symptomatic vasospasm compared with 9.50±2.57ml in those not experiencing symptomatic or angiographic vasospasm [24]. In our case a small amount of IVH was observed, however, no identifiable subarachnoid hemorrhage was present.…”
Section: Discussioncontrasting
confidence: 53%
“…It is defined as clinical neurological symptoms of ischemia (confusion, decreased level of consciousness, focal neurological deficits), with narrowing of cerebral vessels, visualized by computed tomography angiography (CTA). Cerebral vasospasm occur in approximately one third of aSAH patients (Frontera et al, 2009), and the risk of vasospasm is related to the thickness and amount of blood in the subarachnoid space and/or the presence of intraventricular blood assessed on computed tomography (CT), the Fisher grade (Fisher et al, 1980; Jung et al, 2012). The risk of developing cerebral vasospasm is highest during dag 6–8 following ictus (Weir et al, 1978).…”
Section: Introductionmentioning
confidence: 99%